2011
DOI: 10.1159/000324689
|View full text |Cite
|
Sign up to set email alerts
|

Robertsonian Translocation in a Sex Reversal Dog (XX, <i>SRY </i>negative) May Indicate that the Causative Mutation for This Intersexuality Syndrome Resides on Canine Chromosome 23 (CFA23)

Abstract: A Bernese mountain dog was subjected for clinical evaluation due to the presence of ambiguous external genitalia (enlarged clitoris). Anatomical and histological studies revealed the presence of one testicle, one ovotestis and a uterus. This dog was classified as a female-to-male sex reversal, with 2 normal X chromosomes and a lack of the Y chromosome-linked genes SRY and ZFY. It is the first case of this syndrome in this breed. Apparently a Robertsonian translocation, rob(5;23), was also identified in this do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…This intersexuality has been identified to date in more than 20 dog breeds and seems to be a widely distributed DSD in dogs [Meyers-Wallen, 2009;Switonski et al, 2011].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This intersexuality has been identified to date in more than 20 dog breeds and seems to be a widely distributed DSD in dogs [Meyers-Wallen, 2009;Switonski et al, 2011].…”
Section: Discussionmentioning
confidence: 79%
“…Genome scanning of a reference family for the sex reversal syndrome indicated that the causative mutation is located on chromosome 29 [Pujar et al, 2007], but recent studies of an intersex carrying a centric fusion chromosome mutation suggested that it may reside on chromosome 23 [Switonski et al, 2011]. Also, several a priori selected candidate genes were analyzed, but no cosegregating mutation was found [see Switonski et al, 2011]. Searching for a mutation predisposing to cryptorchidism was carried out in Siberian husky dogs.…”
mentioning
confidence: 99%
“…Millis et al (1992) determined the frequency of this disorder at 1.7% in the group of 1345 cats hospitalized in a ten-year period, and Yates et al (2003) reported 1.3% cases of cryptorchidism during a 4.5-year period. While the reversed sex syndrome (78, XX with the occurrence of testis or ovotestis) has been described in many breeds of dogs, such a pathology has not been observed in cats so far (Switonski et al 2011, Christensen 2012. It is suspected that the basis of this anomaly, as in humans or dogs, is a mutation that has not been clearly identified.…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosis of the DSD animals was performed with cytogenetic (identification of sex chromosomes), molecular (detection of the SRY and ZFY genes), and histological (analysis of gonads) techniques as described earlier by Switonski et al [2011].…”
Section: Methodsmentioning
confidence: 99%
“…In our earlier study of a DSD dog carrying a Robertsonian translocation, rob (5; 23), we suggested that the causative mutation could reside on chromosome 23 (CFA23), especially in its pericentromeric region [Switonski et al, 2011]. In silico analysis of the CFA23 sequence revealed 3 positional candidate genes in this region : CLASP2 (cytoplasmic linker associated protein 2), UBP1 (upstream binding protein 1), and FBXL2 (F-box and leucine-rich repeat protein 2) .…”
mentioning
confidence: 99%